Optimalisasi Jadwal Menggunakan Pewarnaan Vertex Graf - Himayati, Ade I. A.; Indriyani, Putri; Bahari, Muhammad F. (Diophantine Journal of Mathematics and Its Applications, 2025)
The preparation of subject schedules at SMP Negeri 2 Karanganyar Demak is still done manually and there are still errors that occur, such as teachers teaching at the same time but in different classes so the schedule is not optimal. This problem can be solved using scheduling techniques through graph coloring using the dot coloring method by substituting subjects in each class as vertices and the relationship between each subject and the subjects of each other class if the teacher who teaches the same subject is expressed as an edge. The algorithm for graph coloring is to determine the chromatic number using a vertex coloring algorithm, that is, using the minimum color type possible without anyone using the same color on neighboring edges. In this article, scheduling is only carried out for class VII at SMP Negeri 2 Karanganyar Demak. Based on the research results, it was found that the minimum number of colors in subject scheduling at SMP Negeri 2 Karanganyar Demak is that the coloring of the class 7 lesson schedule has 78 vertices resulting in 14 colors. Scheduling using point coloring produces a schedule without any overlapping schedules.